Residue quality and N fertilizer do not influence aggregate stabilization of C and N in two tropical soils with contrasting texture - Gentile, R; Vanlauwe, Bernard; Kavoo, A; Chivenge, Pauline P.; Six, Johan (Springer, 2010)
To address soil fertility decline, additions of organic resources and mineral fertilizers are often integrated in sub-Saharan African agroecosystems. Possible benefits to long-term C and N stabilization from this input management practice are, however, largely unknown. Our objectives were (1) to evaluate the effect of residue quality and mineral N on soil C and N stabilization, (2) to determine how input management and root growth interact to control this stabilization, and (3) to assess how these relationships vary with soil texture. We sampled two field trials in Kenya located at Embu, on a clayey soil, and at Machanga, on a loamy sand soil. The trials were initiated in 2002 with residue inputs of different quality (no input, high quality Tithonia diversifolia, medium quality Calliandra calothyrsus, and low quality Zea mays (maize) stover), incorporated at a rate of 4 Mg C ha?1 year?1 alone and in combination with 120 kg N ha?1 season?1 mineral fertilizer. Maize was grown in the plots each season, and a section of the plots was left uncropped. All aboveground maize residues were removed from the plots. Soil samples (0 15 cm) were collected in March 2005 to assess aggregation and C and N stabilization. The fine-textured soil at Embu was more responsive to inputs than the coarse-textured soil at Machanga. Residue additions increased macroaggregation at Embu, and cropping increased aggregation at Machanga. At Embu adding organic residue, regardless of the quality, and cropping significantly increased total soil C and N. This increase was also observed in the macroaggregate and microaggregate-within-macroaggregate fractions. Input treatments had little effect on C and N contents of the whole soil or specific fractions at Machanga. Nitrogen fertilizer additions did not significantly alter C or N content of the whole soil or specific fractions at either site. We conclude that residue quality does not affect the stabilization of soil organic C and N. Inputs of C and soil stabilization capacity are more important controls on stabilization of soil organic matter.